KEKUASAAN DI ATAS PENTAS : LA TRAGÉDIE « PHÈDRE» DALAM PERSPEKTIF FEMINISME POSTSTRUKTURALIS - Wening Udasmoro (Faculty of Cultural Sciences, Universitas Gadjah Mada, 2008)
This article attempts to analyse one of Jean Racine’s famous works entitled Phèdre using the feminist post-structuralist approach, which differs from earlier analysis of his dramas by others. As a classical work, Phèdre has frequently been analysed by many scholars using the structuralist approach, thus specifically concentrating on binary opposition synthesis. As a result, the dichotomous understanding of Phèdre has been produced, and in many instances shows the stereotypical effect of women in many aspects of their lives. In this analysis of Phèdre, the feminist post structuralist approach deconstructs that understanding and revealed that power relation is one of the important perspectives that can be used in illuminating meaning within the text.